PENGARUH KURS RUPIAH, INFLASI DAN SUKU BUNGA TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR JASA SUB KONSTRUKSI DAN BANGUNAN PADA BURSA EFEK INDONESIA - Galih Abi Nugroho; Sri Hermuningsih (Universitas Muhammadiyah Metro Lampung, 2020)
This study aims to determine the effect of the rupiah exchange rate, inflation and interest rates in sub construction and building service companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The nature of this research is a quantitative approach because the data used are in the form of numbers in statistical analysis. The population is construction and building companies listed on the Indonesia Stock Exchange. The sample used was panel data, with time series data of 5 years and cross section data of 12 companies. The sampling technique was obtained by using purposive sampling technique. Data collection techniques using documentation, while data analysis techniques using multiple linear regression analysis supported by the classical assumption test that is normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. In this study also used the Sobel test. Based on the results of data analysis, it shows that: (1) Rupiah exchange rate has a positive and not significant effect on stock return (2) Inflation has a negative and significant effect on stock return (3) Interest rates have a negative and significant effect on stock return, (4) simultaneously, rupiah exchange rate, inflation and interest rates have a significant effect on stock return. The results of the coefficient of determination (R2) of 12.1% while the remaining 87.9% is influenced by other variables outside the model.Keywords: Rupiah Exchange Rate, Inflation, Interest Rates, Stock Return